2013
DOI: 10.1038/srep01713
|View full text |Cite
|
Sign up to set email alerts
|

Do organic and other exotic superconductors fail universal scaling relations?

Abstract: Universal scaling relations are of tremendous importance in science, as they reveal fundamental laws of nature. Several such scaling relations have recently been proposed for superconductors; however, they are not really universal in the sense that some important families of superconductors appear to fail the scaling relations, or obey the scaling with different scaling pre-factors. In particular, a large group of materials called organic (or molecular) superconductors are a notable example. Here, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…60,61 A similar analysis carried out on previously published data, [26][27][28][29][47][48][49][50] in which ρ s (T ) is 4 to 40 times smaller, predicts vortex unbinding in the range 3 to 8 K. This is not observed. Finally, our data have recently been shown to be consistent 62 with the Homes scaling law 63 relating superfluid density to the product of normal-state conductivity and T c .…”
supporting
confidence: 80%
“…60,61 A similar analysis carried out on previously published data, [26][27][28][29][47][48][49][50] in which ρ s (T ) is 4 to 40 times smaller, predicts vortex unbinding in the range 3 to 8 K. This is not observed. Finally, our data have recently been shown to be consistent 62 with the Homes scaling law 63 relating superfluid density to the product of normal-state conductivity and T c .…”
supporting
confidence: 80%
“…To convert to a dimensionless unit system used in be almost the arithmetic mean of the two experimentally determined values. Additionally, one may compare to the most recent results found for organic superconductors in [57], i.e. C = (110 ± 60) cm −1 /Ω −1 K, again in dimensionful units.…”
Section: )mentioning
confidence: 91%
“…Initially, it was thought that the materials that fell on the scaling line were likely in the dirty limit [37]. However, it has been shown that many superconducting materials fall on the scaling line, and many of them are not in the dirty limit [72]. Moreover, it has been recently demonstrated that the scaling relation is more robust than originally thought and should be valid for most materials, including those that approach the clean limit [38], suggesting that the scaling relation is an intrinsic property of the BCS theory of superconductivity.…”
Section: Parameter Scalingmentioning
confidence: 99%